2022
DOI: 10.1111/1365-2745.13978
|View full text |Cite
|
Sign up to set email alerts
|

Timing and duration of drought modulate tree growth response in pure and mixed stands of Scots pine and Norway spruce

Abstract: 1. Climate change is increasing the severity and frequency of droughts around the globe, leading to tree mortality that reduces production and provision of other ecosystem services. Recent studies show that growth of mixed stands may be more resilient to drought than pure stands. The two most economically important and widely distributed tree species in Europe are Norway spruce (Picea abies (L.) Karst) and Scots pine (Pinus sylvestris L.), but little is known about their susceptibility to drought when coexist.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 98 publications
(161 reference statements)
1
3
0
Order By: Relevance
“…4). These results highlight the greater sensitivity of spruce trees forests to increasing VPD 41,42 , and provide early evidence for the reductions in tree growth reported by the Swedish Forest Inventory 16 .…”
Section: Historic Temperature Trends Water Balance and Tree Growthsupporting
confidence: 60%
“…4). These results highlight the greater sensitivity of spruce trees forests to increasing VPD 41,42 , and provide early evidence for the reductions in tree growth reported by the Swedish Forest Inventory 16 .…”
Section: Historic Temperature Trends Water Balance and Tree Growthsupporting
confidence: 60%
“…Mixed forests have several advantages compared to pure stands, such more stable production (del Río et al., 2022), ecosystem service provisioning (Felton et al., 2020), and less vulnerability during drought (Chen et al., 2023; Fichtner et al., 2020). Mixtures of Norway spruce and Scots pine may reduce drought damage risk for both species (Aldea et al., 2022). However, mixtures are more complicated and expensive to manage than monocultures (Coll et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mixtures of Norway spruce and Scots pine might be more resistant to drought than pure stands of either species, although the benefit would depend on the duration of the drought (Aldea et al., 2022). In our study, drought damage risk increased with stem density for both conifers (Figure 1e,f and Figure 3e), which would agree with several studies showing significantly higher tree resilience at lower stem densities (Sohn et al., 2016; Steckel et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From the tree ring collections located at 22 sites in pure and mixed stands of Scots pine and Norway spruce, including Austria and Slovakia, Aldea et al (2022) [22] found that compared to Scots pine, Norway spruce exhibited greater susceptibility to summer dryness, reduced resistance of forest stands, and a more extended recovery period. They further noted that mixed forests offered both species more resistance to drought.…”
Section: Introductionmentioning
confidence: 99%